Boundary element method for the pennes bioheat transfer equation - Muchsin Mohamed (2015)
Finite element method is a commonly used research tool in the fields of engineering, especially in heat transfer. Many researchers have measured the temperature distribution of the eye using this method and they have obtained fruitful results. In this project, the temperature distribution of the eye is measured using the boundary element method. There do already exist results that use the boundary element method. This report uses one such research as a basis but with simplified model of the eye and simplified boundary conditions. The temperature of the eye obtained using boundary element method with the simplified boundary conditions and model is close to the value obtained from a method that uses a more accurate representation of the eye and boundary conditions. The results are also close to those obtained through experiments by researchers. This proves the successfulness of the simplified model and boundary conditions. The values are also proven to be sensitive to the environmental factors, which can be found in the sensitivity analysis. Some possible applications of this thermal distribution of the eye is discussed in the conclusion section. A drawback of this simulation is also discussed.